IMPLEMENTATION OF THE STANDARD STB ISO 7500–1–2008 «MATERIALS METALLIC. CHECK OF UNIAXIAL TESTING MACHINES FOR TESTS AT STATISTICAL LOADINGS. Part 1. Machines for tests for tension/compression. Check and calibration of force measure system» at RUP «BMZ» - I. V. Bujanova; E. V. Borisenko (Литьë и металлургия)
It is shown that introduction of standard ISO 7500-12008 at RUP «BMZ» allowed to meet the requirements of auditors and production consumers to the test equipment, and consequently to the quality of measurable parameters.